Factors affecting the cost of production of milk and milk products of crossbred cows - T. Borpuzari and R. N. Goswami, Jakir Hussain, R. Roychoudhury, T. K. A A. Aziz, B. N. Saikia (Indian Journal of Animal Production and Management, 2019)
The experiment was carried out with10 Jersey crossbred and 10 Holstein-Friesian crossbred cows duringeach of the four seasons viz. Pre-monsoon, Monsoon, Post-monsoon and Winter during the year 2016-17 to study the effect of feeding practice, genetic group and season on the cost of production of milk andmilk products such as paneer and curd (dahi) of crossbred lactating cows reared under organized farmcondition. The overall mean cost of production of milk, paneer and and curd (dahi) was ₹ 31.73±0.55,266.47±2.89 and 84.17±0.75 per kg, respectively. There was highly significant difference (p